THE ROLE OF THE LAITY IN THE HIERARCHICAL STRUCTURE OF THE MALANKARA ORTHODOX SYRIAN CHURCH: A UNIQUE FEATURE OF THE ASIAN CHRISTIAN HERITAGE - Oozhikattu, Dhanyananda (Asian Horizons, 2016)
This article deals with the role of the laity in the hierarchical structure and the whole functioning of the Malankara Orthodox Syrian Church. The origin and development of the Church of St Thomas Christians in the rich religious and cultural milieu of India is depicted as an introduction to the central theme of the evolution of the present fullfledged system of lay participation in the key areas of ecclesial life. No Christian Church other than the Malankara Orthodox Syrian Church has such a history of growth in the midst of world religions as well as in communion and confrontation with other Christian Churches. Her ecclesial heritage is derived from the Mar Thoma Margam. The revolt against the bishops of the Pakalomattam lineage, the demands for the re-introduction of the rights of the laity, the collective deliberation as well as the consequent decisions in furtherance of the democratic ideals and in pursuance of the promotion of the values of the Mar Thoma Margam unfold important episodes of Indian Church history. The extent of the lay participation in the ecclesial life of the Malankara Orthodox Syrian Church is astonishing. The lay people play a decisive role not only in the election of the Catholicos and the Metropolitans, but also in the whole administration of the Church.